Fault Removal Effectiveness On Software Requirements Specification Using Non-Preemptive Relocation Technique (International Journal of Engineering and Computer Science, 2014)
Software specification is defined as the requirements that facilitates to achieve the specified organizational objective without any faults.  Existing Model-based Oracle Software Generation (MOG) method capture the types of faults and define an automatically generated partial, passive oracle from the agent design models. MOG method not yet developed the framework for removing (i.e.,) preventing the fault at the initial stage of the software requirement specification. Present systematic review of requirements specifications from software engineering model fails to integrate the business requirements with the software functional model. To prevent the fault on the initial stage of the software requirement specification, Prior Fault Removal method using the Non-preemptive Relocation (PFR-NR) technique is developed. Prior Fault removal assures the definite software requirement specification without any faults. The functional model in PFR-NR technique refers to the set of software functions which offers a reliable fault free solution while performing the execution process. Non-preemptive Relocation performs the monitoring using the Reactive loop manage mechanism. The looping mechanism performs the integration between the business requirements and software functional model in the non-preemptive relocation technique. Non-preemptive relocation provides 12 % improved result to the customers. PFR-NR technique is measured in terms of Software fault prevention level, Customers satisfaction point, software specification overhead rate, true positive business requirements and software function integration time.